2009
DOI: 10.1039/b821119c
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and bonding properties of lithium naphthalene radical anion, [Li+(TMEDA)2][C10H8˙−], and lithium naphthalene dianion [(Li+TMEDA)2C10H8−2]

Abstract: The crystal structures of lithium naphthalene radical-anion (LiC10H8) and lithium naphthalene dianion (Li2C10H8) are reported, and their bonding properties analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Each scandium ion binds  4 to C1 through C4 (or C1A through C4A) with similar distances averaging 2.51 Å. These features are also reminiscent of those of the lithium naphthalene dianion [Li(TMEDA)]2(- 4 : 4 -C10H8) (TMEDA = tetramethylethylenediamine) (Melero et al, 2009). …”
Section: Scandium Fused-arene Complexes: Synthesis Characterizationmentioning
confidence: 68%
“…Each scandium ion binds  4 to C1 through C4 (or C1A through C4A) with similar distances averaging 2.51 Å. These features are also reminiscent of those of the lithium naphthalene dianion [Li(TMEDA)]2(- 4 : 4 -C10H8) (TMEDA = tetramethylethylenediamine) (Melero et al, 2009). …”
Section: Scandium Fused-arene Complexes: Synthesis Characterizationmentioning
confidence: 68%
“…The X-ray single-crystal structure study revealed that complex 2c similarly to the proline derived diamidobinaphthyl dilithium salt adopts a dimeric structure. 10e In the tetranuclear core of 2c each Li atom is bound to two nitrogen atoms of two different binaphthylamido ligands and at the same time two short contacts 29 Clear single-crystalline samples of 2d suitable for X-ray diffraction studies were obtained by slow diffusion of hexane in a THF solution at −20°C. The molecular structure of 2d is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in Y 2 K 2 -biph, the energy level of the benzene π* orbitals is close enough to the energy level of the empty 4d orbitals of the yttrium(III) ion to induce a covalent bonding interaction and stabilize the high electron density of the benzene tetraanion. Indeed, the geometric parameters are almost identical for dianionic naphthalene complexes of lithium 76 and dianionic naphthalene complexes of rare-earth metals. 49 Inverse sandwich arene complexes of uranium 12,13,26,29,[65][66][67][68][69][70][71][72][73][74][75] are structurally similar to the rare-earth metal stabilized benzene tetraanion, however, most uranium complexes were found to contain a bridging benzene dianion instead of a tetraanion.…”
Section: Tetraanionic Aryl Substituted Benzene Complexesmentioning
confidence: 97%